Is a good colonial conscience still necessary in a modern European country? - (:unkn) unknown (My University, 1991)
Article written in 1988 as a review of the book 'Resenha histórico-militar das campanhas de Africa (1961-1974). Vol.I. Enquadramento geral', published in Lisbon by the General Staff of the Army and typical of the most hackneyed of Lusotropicalisms; the article ends with a broader reflection on the ideology of Portuguese cooperation with Africa.
Keywords: African Research